Wegeners Granulomatosis presenting as a small saft palate mass (Bangladesh Journal of Otorhinolaryngology, 2012)
Wegeners granulomatosis (WG) is a form of vasculitis involves small and medium-sized blood vessels. It commonly involves the upper and lower respiratory tract. However, multisystemic involvement and involvement of kidneys are possible and may lead to a life threatening condition. Therefore early diagnosis is important. Timely beginning of clinical management may considerably influence the further course of disease. Although, it may present as oro-pharyngeal mass surgical procedure is not indicated method of treatment of Wegeners granulomatosis, because it can increase the pathologic process. Here we report a case of Wegeners granulomatosis (WG) presenting as a tissue growth over the soft palate.  DOI: http://dx.doi.org/10.3329/bjo.v18i1.10423Bangladesh J Otorhinolaryngol 2012; 18(1): 74-76